The Role of School Principal Leadership in Managing Educational Human Resources in Tangerang Regency - Endang Hermawan; Sutarman (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
School leadership plays a crucial role in the effective management of educational human resources and the improvement of school performance. The principal, as the leader of the school organization, is responsible for managing teachers and educational staff to ensure the achievement of educational goals. This study aims to analyze the role of school principals in managing educational human resources in schools in Tangerang Regency. The research focuses on several aspects of human resource management, including planning, recruitment, professional development, performance evaluation, and motivation of teachers and educational staff. This study employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving school principals, teachers, and administrative staff. The findings show that effective leadership by school principals significantly contributes to the improvement of human resource management in schools. Principals who demonstrate strong leadership are able to create a supportive work environment, encourage professional development, and enhance the performance and commitment of teachers and staff. In addition, leadership strategies such as supervision, mentoring, and collaborative decision-making play an important role in strengthening the quality of educational management. The study concludes that the leadership of school principals is a key factor in optimizing the management of educational human resources and improving the overall quality of education in Tangerang Regency.